MINHO robot football team for 2001 - Ribeiro, A. Fernando (2002)
This paper describes an autonomous robot football team. The work is being carried out since 1998. It describes the hardware used by the robots, the sensory system and interfaces, as well as the game strategy. Data acquisition for the perception level is carried out by the vision system, and the image processing system is described. Two cameras are used requiring sensorial fu-sion. With this architecture, an attempted is made to make the autonomous ro-bots more real world intelligent. These robots have a kicker with controlled power, which allows passing the ball to a teammate with controlled distance and direction.